2016
DOI: 10.1111/ejn.13465
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological correlates of decision making impairment in multiple sclerosis

Abstract: Although previous studies have shown that patients with multiple sclerosis (MS) may exhibit impaired decision making (DM), the specific neuro-cognitive processes that underlie this deficiency remain unknown. Inefficient DM may occur due to poor option assessment or a deficit in the evaluation of choice outcomes. This study uses, for the first time, the event-related potential (ERP) technique to analyze these DM subprocesses in patients with MS. Sixteen MS patients and nineteen control subjects performed a DM t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 57 publications
3
15
0
Order By: Relevance
“…More recently, researches show that deficit in decision-making is independent of other cognitive changes occurring during the same period 10 , 40 . Consistent with previous studies 19 , 38 , 39 , we did not find any correlation between impaired decision-making in T2DM group and general cognitive impairment, as measured by the MOCA and MMSE. Further studies are needed to address the potential cognitive factor affecting the decisional process in T2DM group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…More recently, researches show that deficit in decision-making is independent of other cognitive changes occurring during the same period 10 , 40 . Consistent with previous studies 19 , 38 , 39 , we did not find any correlation between impaired decision-making in T2DM group and general cognitive impairment, as measured by the MOCA and MMSE. Further studies are needed to address the potential cognitive factor affecting the decisional process in T2DM group.…”
Section: Discussionsupporting
confidence: 91%
“…Previously it was found that decline in general cognitive function may lead to increased difficulty in decision-making in Alzheimer’s disease patients 12 . However, the majority of IGT studies have failed to observe this association in other populations 19 , 38 , 39 . More recently, researches show that deficit in decision-making is independent of other cognitive changes occurring during the same period 10 , 40 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…retrieve and identify information from past memories) [77,78] and in the ability to retain old memories [81,82]. Furthermore, deficits in attention [79,80], information processing, decision making and problem solving [81,83,84] especially during multitasking activities [85], seem to be frequent. Finally, language and verbal fluency are often impaired in MS [75] and these defects manifest in slow speech capacity and slow information processing speed [74].…”
Section: Cognitive Symptomsmentioning
confidence: 99%
“…Secondly, previous studies only evaluated the accuracy measures of the IGT (e.g., total earned money) and neglected other measures that could provide a deeper insight into the processing of affective feedback (e.g., reaction times following winning or losing trials). Finally, most available studies on DM ability in MS employed clinically heterogeneous samples with regard to disease severity and disease course ( 17 , 23 , 24 ). This is particularly problematic given that the rates of CI differ remarkably between relapsing-remitting and progressive disease courses, which may also influence DM performance ( 25 ).…”
Section: Introductionmentioning
confidence: 99%